2015
DOI: 10.1056/nejmoa1415340
|View full text |Cite
|
Sign up to set email alerts
|

Regional Nodal Irradiation in Early-Stage Breast Cancer

Abstract: BACKGROUND Most women with breast cancer who undergo breast-conserving surgery receive whole-breast irradiation. We examined whether the addition of regional nodal irradiation to whole-breast irradiation improved outcomes. METHODS We randomly assigned women with node-positive or high-risk node-negative breast cancer who were treated with breast-conserving surgery and adjuvant systemic therapy to undergo either whole-breast irradiation plus regional nodal irradiation (including internal mammary, supraclavicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
760
5
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,097 publications
(804 citation statements)
references
References 20 publications
(19 reference statements)
25
760
5
14
Order By: Relevance
“…33 That study, which involved 1832 patients with node-positive or high-risk node-negative disease after breast-conserving therapy, showed that regional nodal irradiation was associated with improved disease-free survival and distant disease-free survival. The results of the study by Hennequin et al showed a lack of benefit of regional nodal irradiation; however, that study was smaller than our study and the patients had a poorer outcome (a 10% lower rate of overall survival at the 5-year follow-up and a 20% lower rate of overall survival at the 10-year follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…33 That study, which involved 1832 patients with node-positive or high-risk node-negative disease after breast-conserving therapy, showed that regional nodal irradiation was associated with improved disease-free survival and distant disease-free survival. The results of the study by Hennequin et al showed a lack of benefit of regional nodal irradiation; however, that study was smaller than our study and the patients had a poorer outcome (a 10% lower rate of overall survival at the 5-year follow-up and a 20% lower rate of overall survival at the 10-year follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…AMAROS work and posteriorly MA-20 15 presented a conflict regarding the extension of radiotherapy treatment of drainage chains 16 . In those studies, patients were submitted to specific treatment of arm pit, supra-clavicular fossa and internal mammary chains (MA-20), while Z0011 used radiotherapy only in tangent fields, in most women.…”
Section: Discussionmentioning
confidence: 99%
“…This trial of extended field adjuvant radiation after a mastectomy initially reported an impressive and significant benefit in DRFS in 2011 [11]. When the 10-year results were reported in 2015, however, the difference in OS was minimal and not significant [12]. The explanation for the failure of DRFS to predict OS remains unclear.…”
Section: Endpoints For Adjuvant Breast Cancer Trials and Eligibility mentioning
confidence: 99%